Analysis of Rice Imports in Indonesia: AIDS approach - Agus Widarjono (Journal of Economics, Business, and Accountancy Ventura, 2018)
Rice is a staple food for Indonesian households. After achieving self-sufficiency of rice in 1984, Indonesia still had to import rice because the domestic rice consumption always exceeded the domestic rice production.Â  This study attempts to analyze a rice import during the 1998-2014 period. The rice import was analyzed based on the main partner of Indonesian rice imports encompassing of Vietnam, Thailand, USA, Other countries. This research applied the demand system method using Almost Ideal Demand System (AIDS). The results indicate that price elasticity of rice import from Vietnam and Thailand was inelastic while from other countries, they were elastic. Based on the expenditure elasticity of rice import, rice is the normal goods for rice import from Thailand and USA. The policy simulation shows that the increase in the price of rice import leads to the decrease of rice import.Â  However, rice import from certain countries such as Thailand still increase. Rice is the staple food, therefore, the government must set up policy to increase domestic rice production for reducing dependency on rice imports.